Outcome-based health education: Possible approaches and models of competence - Martínez-Clares, Pilar; Martínez-Juárez, Mirian; Muñoz-Cantero,, Jesús Miguel (RELIEVE – Electronic Journal of Educational Research and Evaluation, 2014)
The great changes taking place in society today call into question traditional training, which is focused on the transmission of knowledge and training skills. Some experts suggest that the introduction of a competency-based approach to training has presented it with an avenue for modernization and cooperation with the needs of the organizational environment. The approach of Outcome Based Education is considered one of the most important changes in health education for the twenty-first century. This approach is predominant in higher education institutions around the world and is the method recommended by major governing bodies and evaluators of health education (or, in a narrower sense, medical education).